(untitled) (Shimmering Words: Research and Pedagogy E-Journal, 2020)
Going through these moments of progress and development, companies are required to review their structures: administrative, economic, financial, relations with the complexity of human resources, among others, in order to evaluate them and verify if they fulfilling their strategies of action and social responsibility. That is, see if your business management model is consistent with the reality of the market. Two situations must face the economic entities as a challenge of their corporate permanence, first, adapt with a new model of management work according to the management of the variables of innovation, transformation and adaptability; and second, to follow conventionally and let their investment process vanish in the onslaught of the maelstrom of businesses that improve their competitiveness in their desire to conquer in the market. Andean philosophy, anthropology, ethics and theology as a compendium of popular wisdom (ancestral knowledge) of the Andean runa (Andean man), underpin a new theoretical construct of how to manage and lead social and productive organizations, which are generated in the field of the education. Pedagogy, andragogy and hodogogy as dynamic elements of this approach consolidate the vision of responsibility between science and wisdom. The principles of Andean science, elevated at the theoretical level and pragmatized in the experience of the peoples solving specific problems of that reality, have allowed identifying efficient working models in the achievement of strategic goals and objectives. Relieving this option of ancestral knowledge or Andean wisdom, is not to position a vision of racial contempt or revenge, to other perspectives of scientific and technological development, but rather so that with synergy work from this concrete possibility of life and scientism western, companies with their management model nurture each other and consolidate a drive to build a competitive advantage thinking about the sustainability of different organizations, which seek to improve the quality of life; in pursuit of continuing to generate, the wealth of a territory, appropriate to a business model, a tool that "determines the way in which a business creates, provides and captures value" (Osterwalder y Pigneur 2012, pág. 14).